Breaking the cycle of deprivation: an experimental evaluation of an early childhood intervention - Doyle, Orla (Statistical and Social Inquiry Society of Ireland, 2012)
Deprivation early in life has multiple long term consequences for both the individual and society. An increasing body of evidence finds that targeted, early interventions aimed at at-risk children and their families can reduce socioeconomic inequalities in children?s skills and capabilities. This paper describes a randomised control trial (RCT) evaluation of a five-year preventative programme which aims to improve the school readiness skills of socioeconomically disadvantaged children. The Preparing for Life (PFL) programme is one of the first studies in Ireland to use random assignment to experimentally modify the environment of high risk families and track its impact over time. This paper describes the design and motivation for the study, the randomisation procedure adopted and the baseline data collected. Using Monte Carlo permutation testing, it finds that the randomisation procedure was successful as there are no systematic differences between the treatment and control groups at baseline. This indicates that future analysis of treatment effects over the course of the five year evaluation can be causally attributed to the programme and used to determine the impact of Preparing for Life on children?s school readiness skills.
Barrington Lecture read before the Society, 18 April 2012
Keywords: early childhood intervention; RCT; school readiness; permutation testing; 314.15